KANDUNGAN ROS DAN Apo B-100 SERUM, SERTA INDEKS ATEROGENIK TIKUS PUTIH (Rattus norvegicus Berkenhout, 1769) HIPERLIPIDEMIA DENGAN ASUPAN PELET NASI DAN BEKATUL BERAS HITAM (Oryza sativa L.) âCEMPO IRENGâ - , NOOR NAILIS SAADAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Diet with high lipids cause hyperlipidemia. Hyperlipidemia stimulate leukocytes to produce ROS (Reactive Oxygen Species) thereby increasing LDL oxidation. Macrophages phagocytosis oxidized-LDL and form plaque. Black rice has high fiber and anthocyanin, which act as antioxidants and can repair the hyperlipidemia condition. The purpose of this study was to determine the content of ROS, Apo B-100, and atherogenic index of hyperlipidemic Wistar rats (Rattus norvegicus Berkenhout, 1769) which consumed rice and bran of black rice (O. sativa L.) âCempo Irengâ. The research had done with pre and post test randomized control group design. Rats had given a mixture of lard and duck egg yolk (1:1), and pure cholesterol (2% of total volume) orally as much as 1% of body weight (BW) for 30 days. After hyperlipidemia achieved, rats divided into 4 group: normal rats, hyperlipidemic rats, hyperlipidemic rats fed a diet of 30% black rice pellet, and hyperlipidemic rats fed a diet of 10% black rice bran. Blood samples were collected when rats in hyperlipidemia conditions and after treatment with black rice for 30 days. Data of total cholesterol and HDL-Cholesterol level, atherogenic index, ROS, and Apo B-100 level analyzed using ANOVA followed by Tukey test at 5% significance level. The result showed that feeding pellet of rice and bran of black rice \"Cempo Ireng\" in hyperlipidemic rats provide unsignificant difference (p>0.05) on the contents of ROS and Apo B-100 blood serum, but decreased total cholesterol and increased of HDL-cholesterol levels significantly (p<0.05), so the atherogenic index also decreased significantly. Decreasing atherogenic index of hyperlipidemic rats which fed black rice bran pellets is higher than rats which fed black rice \"Cempo Ireng\" pellets. Total cholesterol levels were positively correlated with the atherogenic index, whereas HDL-cholesterol was negatively correlated with the atherogenic index. On the other side, the levels of ROS and Apo B-100 were less associated with atherogenic index. Key words : Hyperlipidemia, Atherogenic index, ROS, Apo B-100, Black rice âCempo Irengâ